Legal position of the issues associated with main contractor's insolvency - Ng, Sock Hooi (2006)
The East Asian Financial crisis has resulted in long-term financial difficulties, which translated into high level of insolvency especially in the sector of construction. Among the construction insolvency, the insolvency of a main contractor is the frequent occurrence. This has brought issues or problems to the sub-contractor who would become unsecured creditors in the event of main contractor's insolvency. The aim of this study is to determine the legal positions relating to issues faced by sub-contractor in the event of main contractor's insolvency. The issues that commonly arise are direct payment, retention fund, setoff, materials and goods, determination, novation etc. However, this study would only focus on the legal positions of the critical issues specifically: direct payment, retention fund, unfixed materials and goods, set-off and determination. The critical issues are those issues that are commonly arising. There are valid and invalid positions for each of the issue arise. For example, the valid position in direct payment means that the employer entitled to pay sub-contractor direct. While, invalid position is the sub-contractor not entitle to be paid directly by employer. The legal positions for each issue can protect the interaction of sub-contractor in the event of main contractor's insolvency. Therefore, the sub-contractor can use this study as guidance when dealing with those issues